Role of Renal Sympathetic Nerve Activity in Volatile Anesthesia's Effect on Renal Excretory Function. Issue 6 (20th August 2021) - Taavo, Micael; Rundgren, Mats; Frykholm, Peter; Larsson, Anders; Franzén, Stephanie; Vargmar, Karin; Valarcher, Jean F; DiBona, Gerald F; Frithiof, Robert
Abstract: Regulation of fluid balance is pivotal during surgery and anesthesia and affects patient morbidity, mortality, and hospital length of stay. Retention of sodium and water is known to occur during surgery but the mechanisms are poorly defined. In this study, we explore how the volatile anesthetic sevoflurane influences renal function by affecting renal sympathetic nerve activity (RSNA). Our results demonstrate that sevoflurane induces renal sodium and water retention during pediatric anesthesia in association with elevated plasma concentration of renin but not arginine–vasopressin. The mechanisms are further explored in conscious and anesthetized ewes where we show that RSNA is increased by sevoflurane compared with when conscious. This is accompanied by renal sodium and water retention and decreased renal blood flow (RBF). Finally, we demonstrate that renal denervation normalizes renal excretory function and improves RBF during sevoflurane anesthesia in sheep. Taken together, this study describes a novel role of the renal sympathetic nerves in regulating renal function and blood flow during sevoflurane anesthesia. Graphical Abstract: